Temporal–Spatial Evolution of Regional Policy Mix Configuration Paths for the Sustainable Development of the New Energy Vehicle Industry Based on the Industrial Ecosystem - Qin Liu; Xun Xu; Ruming Chen; Lvcheng Li (Systems)
The sustainable development of the new energy vehicle (NEV) industry necessitates the dynamic optimization of policies tailored to local circumstances. However, certain regional policies may face ineffectiveness and demand urgent attention and adjustment. This study aims to promote the sustainable development of the NEV industry by dynamically optimizing and adjusting regional policies and policy environments. This research delves into the dynamic joint effect of regional policies and policy environments on sustainable development from the perspective of the industrial ecosystem. First, this study dynamically reveals China’s cross-regional policy intensity’s evolutionary differences through improved word embeddings. Secondly, it further compares dynamic differences in configuration paths of regional policy mixes and policy environments through dynamic Qualitative Comparative Analysis and Necessary Condition Analysis. Finally, it uncovers dynamic changes and differences in the necessity degree of various elements in cross-regional configuration paths. Key findings include the following: (1) The joint effect of policy mixes and policy environments can promote sustainable development of the NEV industry. (2) There exists spatial heterogeneity in each region’s configuration paths for sustainable development of the NEV industry. The Eastern region of China has rich configuration paths, while those in other regions are relatively few. (3) The configuration paths across regions change dynamically, showing four evolutionary trajectories: shifting, oscillating, emerging, and sustained.